2013
DOI: 10.1637/10456-112612-resnote.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spray Escherichia coli Vaccine on the Immunity of Poultry

Abstract: Avian pathogenic Escherichia coli is a current problem in the poultry industry, causing mortality and economic losses. This paper evaluates the dynamics in immune response after the use of spray vaccination against E. coli and, thereby, seeks to understand how the vaccine can provide protection. During the early stages of response to vaccination the presence of antigen-presenting cells is predominant, but these diminish within the first 7 days after vaccination. The immune correlate of protection of vaccinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…The combination of live and autogenous vaccines seems to have triggered a wider immunization spectrum, as observed in turkeys by Sadeyen et al [ 43 ]. In commercial broilers, the immune response produced by a spray live vaccine against E. coli is mainly a cellular response, especially relevant to the sites in contact with the pathogen, as indicated by data obtained by Filho et al [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of live and autogenous vaccines seems to have triggered a wider immunization spectrum, as observed in turkeys by Sadeyen et al [ 43 ]. In commercial broilers, the immune response produced by a spray live vaccine against E. coli is mainly a cellular response, especially relevant to the sites in contact with the pathogen, as indicated by data obtained by Filho et al [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, whilst live-attenuated mutants of various kinds can confer resistance against APEC in target host species [ 21 , 22 , 30 , 42 - 44 ], the innate and cell-mediated responses they elicit are ill-defined. Studies by Fernandez Filho et al [ 43 ] with Poulvac® E. coli only examined peripheral cellular responses to vaccination, with a fine spray, of day-old chicks. No booster was given to those birds at 7 days of age via drinking water as is recommended [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent field trial of Poulvac® E. coli [ 42 ] also supports that giving a booster in drinking water is not necessary. Interestingly, a higher level of peripheral B lymphocytes was detected in the control than the vaccinated group and the authors speculated that Poulvac® E. coli may suppress humoral responses and that they may therefore be dispensable in protection [ 43 ]. In support of this, Salehi et al [ 44 ] also reported a lack of significant induction of antibody response in chickens after aerosol administration of an independent aroA mutant of E. coli .…”
Section: Discussionmentioning
confidence: 99%
“…The same animals were studied throughout the experiment, allowing a continuous analysis of the fluctuation of immune parameters. Flow cytometry was performed as previously described [14]. Briefly, mononuclear cells from peripheral blood were separated by Histopaque-1077 (Sigma).…”
Section: Assessment Of Immune Parameters-cellular Immune Response Anamentioning
confidence: 99%